Screening of Microorganisms and Raw Materials for Lipase Production by Solid-State Fermentation - Grety Márquez Peñamaría; Giselle Morell-Nápoles; Mario Cujilema-Quitio; Gualberto Leon; Patrick Fickers; Luis B. Ramos-Sánchez (Journal of Basic & Applied Sciences, 2017)
The production of biodiesel from vegetable oils using eco-friendly processes is a hot topic actually. These processes are based on enzymatic biocatalysts, namely lipases, and present many advantages over classical processes i.e. they do not require the use of sodium hydroxide, nor huge quantities of water. Lipases are widespread in nature, being produced by many microorganisms. However, fungal lipases have benefits over bacterial lipases due to their low cost of production, thermal and pH stability, substrate specificity and activity in organic solvents. These low cost production processes rely, most of the time, on solid-state fermentation (SSF). The aim of this research was to select microorganisms for their ability to secrete lipolytic enzymes and to grow on a solid support compatible with SSF. Thirty-five yeast and mold strains were tested in term of growth rate and extracellular lipase production. Different solid support such as vermiculite, crushed wheat husk, cacao seed-husk and carbon sources such as soy oil, sunflower oil, olive oil or sucrose were also tested for their ability to support cell growth and lipase production.